Efficacy of statins for osteoporosis: a systematic review and meta-analysis. Issue 1 (January 2017) - An, T.; Hao, J.; Sun, S.; Li, R.; Yang, M.; Cheng, G.; Zou, M.
Abstract Our meta-analysis assessed the efficacy of statins on the risk of fracture, bone mineral density (BMD), and the markers of bone metabolism by collecting data from 33 clinical trials. We found that statin treatment was associated with bone metabolism. And statins seemed to be more effective on male patients with osteoporosis. The efficacy of statins for the treatment of osteoporosis has been controversial in previous studies and meta-analyses. Our meta-analysis was conducted to examine in detail the efficacy of statins on osteoporosis. We searched PubMed, Embase, and the Cochrane Library databases for clinical trials from inception to May 2016. We included studies that described the effect of statins on the risk of fracture, BMD, or bone turnover markers. Moreover, we also conducted subgroup analyses according to the skeleton site, patient gender, and length of follow-up. A total of 33 studies which included 23 observational studies (16 cohort studies and 7 case-control studies) and 10 randomized controlled trials (RCTs) were evaluated. These 33 studies included 314, 473 patients in statin group and 1, 349, 192 patients in control group. Statins decreased the risk of overall fractures (OR = 0.81, 95% CI 0.73–0.89) and hip fractures (OR = 0.75, 95% CI 0.60–0.92). Furthermore, the use of statins was associated with increased BMD at the total hip (standardized mean difference (SMD) = 0.18, 95% CI 0.00–0.36) and lumbar spine (SMD = 0.20, 95% CI 0.07–0.32) and improved the bone formation marker, osteocalcin (OC) (SMD = 0.21, 95% CI 0.00–0.42). However, there was no positive effect on vertebral fractures, upper extremity fractures, BMD at the femoral neck, bone-specific alkaline phosphatase (BALP), and serum C-terminal peptide of type I collagen (S-CTX). Also, compared with male subgroups, the effect on female subgroups was only slightly positive or of no statistical significance. Our meta-analysis indicates that statin treatment may be associated with a decreased risk of overall fractures and hip fractures, an increased BMD at the total hip, BMD at the lumbar spine, and OC. Moreover, our results also show that statin treatment may have a greater effect on male patients than on female patients.